(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
This research has as its main objective to analyze the strategic use of information sources for Knowledge Management, from the perspective of the role played by events. It explains about the concepts that permeate KM and how information sources, especially regarding events, can be used strategically in the consolidation of an organization focused on learning and capable of managing its knowledge. As a methodological foundation, this research is bibliographic, descriptive-exploratory, and uses a qualitative approach. As a result, it is expected to elucidate the function and the relevance of events in the context of Knowledge Management and to explain about their strategic role as a source of information in the generation of organizational knowledge.